Effect of exogenous human chorionic gonadotropin on ovulation in mice - S. Ya. Amstislavsky; S. V. Ranneva; D. S. Ragaeva; E. A. Chuyko; A. M. Popkova; E. Yu. Brusentsev (Вавиловский журнал генетики и селекции, 2020)
The implementation of assisted reproductive technologies (ART), hormonal stimulation in particular, may change the quality of ovulated oocytes. The purpose of our work was to study ovulation in CD1 mice after their stimulation with human chorionic gonadotropin (hCG) and to investigate the effects of such hormonal stimulation on the pregnancy duration, fetal losses and the weight of the offspring. No significant differences were found in the total number of ovulated oocytes or in the number of immature (without a polar body) ovulated oocytes; nor were there differences between the groups in the number of oocytes with a developing polar body. However, the number of matured oocytes with a distinct polar body was significantly higher (p < 0.05) in mice stimulated with hCG (experimental group) as compared with the controls (6.2 ± 0.86 and 2.2 ± 0.97, respectively). No significant differences were observed between the experimental and control mice in the duration of pregnancy or in the numbers of term offspring, including the percentage of live and stillborn pups. However, the body weight of the offspring in the experimental group was significantly lower (p < 0.001) as compared with the controls on the fifth day after birth (3.16 ± 0.09 and 3.76 ± 0.07, respectively). Thus, exogenous hCG facilitates the development of mouse oocytes in vivo, which leads to the larger number of their mature forms at ovulation, however, the offspring born after hCG-stimulated pregnancy was characterized by a lower body weight on the fifth day after birth.